Perancangan Sistem Informasi Pemasaran Jasa Pada Difa Make-Up & Decoration Berbasis Web Menggunakan Bahasa Pemrograman PHP - Mansyuri, Umar; Arief, Rahadian; Farhan Fauzan, Achmad; Dwiki Putra Aryono, Gagah; Hidayat, Amat (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
This study discusses the development and implementation of a web-based marketing information system for Difa Make-Up & Decoration. Using the prototyping method, this research aims to address the issues faced by Difa Make-Up & Decoration in managing marketing and service bookings. The system is designed to enhance online visibility, modernize business operations, and open new opportunities for growth. The developed information system includes features such as an interactive online catalog, real-time booking system, efficient customer data management, and analytical tools for strategic decision-making. This Wedding Organizer information system uses PHP and MySQL programming languages. The development method used for this system is prototyping, which consists of analysis, design, application development, evaluation, and results. The results of the study show that this system successfully improves operational efficiency and market reach. Thus, this research significantly contributes to the digital transformation in the creative services sector and enhances the competitiveness of SMEs in the wedding industry